2012
DOI: 10.3347/kjp.2012.50.2.133
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Leishmaniasis Mimicking Autoimmune Hepatitis, Primary Biliary Cirrhosis, and Systemic Lupus Erythematosus Overlap

Abstract: Visceral leishmaniasis (VL) is a life-threatening infection caused by Leishmania species. In addition to typical clinical findings as fever, hepatosplenomegaly, and cachexia, VL is associated with autoimmune phenomena. To date, VL mimicking or exacerbating various autoimmune diseases have been described, including systemic lupus erythematosus (SLE), rheumatoid arthritis, and autoimmune hepatitis (AIH). Herein, we presented a patient with VL who had overlapping clinical features with SLE, AIH, as well as antimi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 10 publications
0
32
0
Order By: Relevance
“…From another perspective, autoimmune phenomena is more described in VL patients, probably due to the exposure of self antigens as a consequence of tissue destruction caused by the parasite . Another possible mechanism is polyclonal activation of B cells by VL; this process does not require direct stimulation of T cells and can be achieved through other inflammatory cells …”
Section: Discussionmentioning
confidence: 99%
“…From another perspective, autoimmune phenomena is more described in VL patients, probably due to the exposure of self antigens as a consequence of tissue destruction caused by the parasite . Another possible mechanism is polyclonal activation of B cells by VL; this process does not require direct stimulation of T cells and can be achieved through other inflammatory cells …”
Section: Discussionmentioning
confidence: 99%
“…Different regimens of Ambisome® have been recommended for treatment of kala-azar [12,13,14]. The regimen which is usually administered in immunocompetent pediatric patients was scheduled for our patient [14,15]. …”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, the fever resolved and on her follow-up examination the patient was in good clinical condition with normal blood counts and was also SMA negative and showed only low titer ANA and AMA [84]. The authors conclude that the observed features of AIH, PBC, and SLE might have been caused due to the high amount of self antigens released during the Leishmania-induced tissue destruction [84]. Thus, a variety of autoantibodies normally associated with autoimmune diseases, such as AIH, PBC, SLE, and RA may be found in the serum and may under certain circumstances even precipitate underlying autoimmune conditions.…”
Section: Pathogens and Autoimmune Hepatitis mentioning
confidence: 95%
“…She displayed significant erythema and arthritis at ankles, wrists, and hand joints. In addition, her serum aminotransferase levels were slightly elevated and she was found positive for ANA, SMA, and AMA, but negative for LKM and other AIH autoantibodies [84]. A subsequent liver biopsy revealed robust plasma cell and lymphocyte infiltrations displayed in an interface hepatitis pattern.…”
Section: Other Pathogensmentioning
confidence: 98%
See 1 more Smart Citation